Քեսապի հայոց սրբացուած ծառերը - Չոլաքեան, Յակոբ (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
У местных армян в районе Кесаб священными считаются пробковый дуб, платан, лавровое дерево и маслина. Пробковый дуб символизирует святилище, и по поверьям сельских жителей человекоподобный дух Гихитсиг Бабуг охраняет дерево. Лавровое дерево и маслина, как исполняющие обеты и тем более просьбы о деторождении, считаются святыми деревьями. У родников под платаном отмечаются торжества, празднования и всенародные паломничества. Эти деревья являются общественной собственностью и защищаются силой предания. In the Kesap region, the evergreen oak, platan, laurel and olive trees are considered sacred by native Armenians. The evergreen oak is a tree symbolizing the sanctuary, and according to the beliefs of the villagers, it is protected by Kighitsik Papuk, who is the spiritual anthropomorphic guardian of the sanctuary. The laurel and olive tree are considered sacred trees for the fulfillment of many wishes, but especially for the birth of a child. Ceremonies, festivals and popular pilgrimages are held under the platan tree near the springs. They are public properties and are traditionally protected.
Keywords: Հաղորդումներ; Քեսապ; Սրբազան ծառերի պաշտամունք